Susceptible and resistant olive cultivars show differential physiological response to Xylella fastidiosa infections - Surano, Antony; Abou Kubaa, Raied; Nigro, Franco; Altamura, Giuseppe; Losciale, Pasquale; Saponari, Maria; Saldarelli, Pasquale (Frontiers in Plant Science, 2022)
Olive quick decline syndrome (OQDS) is a severe disease, first described in Italy in late 2013, caused by strains of Xylella fastidiosa subsp. pauca (Xfp) in susceptible olive cultivars. Conversely, resistant olive cultivars do not develop OQDS but present scattered branch dieback, which generally does not evolve to severe canopy decline. In the present study, we assessed the physiological responses of Xfp-infected olive trees of susceptible and resistant cultivars. Periodic measurements of stomatal conductance (gs) and stem water potential (Ψstem) were performed using a set of healthy and Xfp-infected plants of the susceptible “Cellina di Nardò” and resistant “Leccino” and “FS17” cultivars. Strong differences in Δgs and ΔΨstem among Xfp-infected trees of these cultivars were found, with higher values in Cellina di Nardò than in Leccino and FS17, while no differences were found among healthy plants of the different cultivars. Both resistant olive cultivars showed lower water stress upon Xfp infections, compared to the susceptible one, suggesting that measurements of gs and Ψstem may represent discriminating parameters to be exploited in screening programs of olive genotypes for resistance to X. fastidiosa.